Expectations, Uncertainty, and Monetary Policy - Kjellberg, David (Uppsala universitet, Nationalekonomiska institutionen, 2007)
Essay 1 - To evaluate measures of expectations I examine and compare some of the most common methods for capturing expectations: the futures method which utilizes financial market prices, the VAR forecast method, and the survey method. I study average expectations on the Federal funds rate target, and the main findings can be summarized as follows: i) the survey measure and the futures measure are highly correlated; the correlation coefficient is 0.81 which indicates that the measures capture the same phenomenon, ii) the survey measure consistently overestimates the realized changes in the interest rate, iii) the VAR forecast method shows little resemblance with the other methods. Essay 2 - This paper takes a critical look at available proxies of uncertainty. Two questions are addressed: (i) How do we evaluate these proxies given that subjective uncertainty is inherently unobservable? (ii) Is there such a thing as a general macroeconomic uncertainty? Using correlations, some narrative evidence and a factor analysis, we find that disagreement and stock market volatility proxies seem to be valid measures of uncertainty whereas probability forecast measures are not. This result is reinforced when we use our proxies in standard macroeconomic applications where uncertainty is supposed to be of importance. Uncertainty is positively correlated with the absolute value of the GDP-gap. Essay 3 - The co-movements of exchange rates and interest rates as the economy responds to shocks is a potential source of deviations from uncovered interest rate parity. This paper investigates whether an open economy macro model with endogenous monetary policy is capable of explaining the exchange rate risk premium puzzle. When the central bank is engaged in interest rate smoothing, a negative relationship between exchange rate changes and interest differentials emerge for realistic parameter values without assuming an extremely large and variable risk premium as done in previous studies. Essay 4 - This paper shows how market expectations as a function of the forecasting horizon can be constructed and used to analyse issues like how far in advance monetary policy actions are anticipated and how the market’s understanding of monetary policy has developed over time. On average about half of a monetary policy action is anticipated one month before a policy meeting. The share of fully anticipated FOMC policy decisions increase from less than 10% at the two-month horizon, to about 70% at the one-day horizon. The market ability to predict policy has improved substantially after 1999 as the fraction of fully anticipated meetings has quadrupled at the monthly horizon. This improvement can be described as an effect of increased central bank transparency.